Perception-action interaction and bissection - Elton Matsushima; Paula Chiaretti; Daniel Kreling; Murilo Lima; José Aparecido Da Silva; Nilton Ribeiro-Filho (Paidéia (Ribeirão Preto), 2004)
Several studies using visually directed actions as indicators of perceived distance showed that people could accurately walk toward targets far up to 22m. Those results, summed up to those related to perceptual measures of perceived distance, showed that those responses were controlled by a single internal variable, namely visually perceived location. In the present study, we compared performance in bisection tasks, performed by open-loop walking or by perceptual matching. Observers (N=20) walked toward or adjust a pointer to the mean point of an egocentric distance (5, 10 or 15m), under binocular viewing. Results indicated accuracy on both responses, with no reliable differences between them, supporting the hypothesis of a single internal variable controlling action and perception. This invariant may be determined by a weighted set of sources of information.